Efficacy of an online lung ultrasound module on skill acquisition by clinician: a new paradigm - Sharma, Alok; Kumar, Gunjana; Nagpal, Rema; Naranje, Kirti; Sengupta, Arnab; Jagannath, Vanitha; Suryawanshi, Sonali; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2024)
Abstract: Introduction: Lung ultrasound (US) as an assessment tool has seen significant expansion in adult, pediatric, and neonatal populations due to advancements in point-of-care ultrasound over the past two decades. However, with fewer experts and learning platforms available in low-middle-income countries and the lack of a standardised supervised training program, lung US is not currently effectively used to the best of its potential in neonatal units. Methodology: A cross-sectional survey assessed the efficacy of learning lung US via a mentor-based online teaching module (NEOPOCUS). The questionnaire comprised the clinicians' demographic profile, pre-course skills and self-assessment of skill acquisition after course completion with ongoing hands-on practice. Results: One hundred seventy-five clinicians responded to the survey, with the majority (87.9%) working in level 3 and 4 NICUs. Clinicians had variable clinical experience. 53.2% were consultant paediatricians/neonatologists with over ten years of experience. Following the course, there was a significant increase in clinician confidence levels in diagnosing and assessing all lung US pathology, as evidenced by the increase in median cumulative scores [from baseline 6 (IQR 6-9) to 20 (IQR 16-24), p<0.001] with half of them gaining confidence within three months of the course. Conclusion: An online curriculum-based neonatal lung ultrasound training programme with clinician image demonstration and peer review of images for image optimisation increases self-reported confidence in diagnosing and managing neonatal lung pathology. Web-based online training in neonatal lung ultrasound has merits that can help with the delivery of training globally, and especially in low and middle-income countries.